THE EFFECT OF HONEY SUPPLEMENTATION ON AN. B WITH COUGH PROBLEM WITH MEDICAL DIAGNOSIS OF BRONCHOPNEUMONIA AT RS. HJ BUNDA HALIMAH - Karlina Karlina (ALINEA: Health Science & Medical International Journal, 2024)
Bronchopneumonia is where the respiratory system, namely the lungs, becomes inflamed. In this disease, the target is the respiratory tract, bronchi to the pulmonary alveoli; the manifestation of this form of attack in bronchopneumonia disease has several variations, namely in the form of cough, runny nose, and fever, with accompanying tightness. This study used a case study method; the data collected in this study were carried out before and after the intervention was given to overcome the problem of Bronchopneumonia on February 10, 204, at 15.50 WIB, namely by providing honey as much as 2.5 ml given 1x1 at night 30 minutes before bedtime carried out for 3 days. The assessment recorded in this study is the patient's condition and what the client complains about. After that, the patient's vital signs are observed, measuring the frequency of coughing. In the statement of coughing very often, it can be stated that the cough is severe, and the statement never said that the patient does not have a cough. The assessment results are recorded in the observation sheet, and the examination is carried out 3 times a day. In this case study, the authors will take midwifery care actions by giving honey supplementation, which aims to increase the frequency of coughs experienced by An. B, who is 2 years old with a diagnosis. B is 2 years old with a medical diagnosis of Bronchopneumonia for 3 days. The conclusion of this study is to provide honey supplements that aim to reduce the frequency of cough experienced by An. B with a medical diagnosis of Bronchopneumonia.